Energy-efficiency maximization scheme for data collection in wireless power communication networks - Haijiang GE; Zhanwei YU; Kaikai CHI (Dianxin kexue)
WPCN composed of multiple RF energy sources and sinks was studied.The energy efficiency of data collection were maximized by jointly optimizing the transmission power of energy sources,the time allocation of wireless energy transfer and the time allocation of nodes’ data transmission.Specifically,the energy efficiency maximization problem was modeled firstly.Then,the optimal value of transmitted power was obtained,and the monotonicity of energy-efficiency function and the convexity of throughput function were further deduced.Finally,based on these properties,an efficient algorithm which combines golden-section search and bisection search was designed to get the optimal solution quickly.The simulation results show that the proposed optimal algorithm can significantly improve the energy efficiency compared with the baseline scheme.